Search for anomalous Wtb couplings and flavour-changing neutral currents in t-channel single top quark production in pp collisions at √s=7 and 8 TeV - Khachatryan, V.; Sirunyan, A. M.; Tumasyan, A.; Adam, W.; Asilar, E.; Bergauer, T.; Brandstetter, J.; Brondolin, E.; Dragicevic, M.; Eroe, J.; Flechl, M.; Friedl, M.; et al. (SPRINGER, 2017)
Single top quark events produced in the t channel are used to set limits on anomalous Wtb couplings and to search for top quark flavour-changing neutral current (FCNC) interactions. The data taken with the CMS detector at the LHC in proton-proton collisions at and 8 TeV correspond to integrated luminosities of 5.0 and 19.7 fb(-1), respectively. The analysis is performed using events with one muon and two or three jets. A Bayesian neural network technique is used to discriminate between the signal and backgrounds, which are observed to be consistent with the standard model prediction. The 95% confidence level (CL) exclusion limits on anomalous right-handed vector, and left- and right-handed tensor Wtb couplings are measured to be vertical bar f (V) (R) vertical bar is the scale for new physics, and correspond to upper limits on the branching fractions of 2.0 x 10(-5) and 4.1 x 10(-4) for the decays t -> ug and t -> cg, respectively.
Keywords: Flavour Changing Neutral Currents; Hadron-Hadron scattering (experiments); Top physics; STANDARD; HIGGS; DECAYS; MODELS; Physics